Refugees and the myth of human rights life outside the pale of the law - Larking, Emma (Ashgate Pub., 2014)
Refugees and the Myth of Human Rights combines philosophical, historical, and legal analysis to clarify the key concepts at stake in the debate, and to demonstrate the threat posed by contemporary border regimes to rights protection and the rule of law within liberal democracies.